Comparison of 2 chromogenic media for the detection of extended-spectrum β-lactamase producing Enterobacteriaceae stool carriage in nursing home residents - Blane, Beth (Diagn Microbiol Infect Dis, 2016)
ChromID ESBL agar and Brilliance ESBL agar were compared for the isolation of extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae from 298 stools. These had comparable sensitivity and selectivity for the 116 positive samples. Pre-enrichment with cefpodoxime and extending incubation to 48 hours after direct plating both significantly increased sensitivity but reduced selectivity of both agars.